New records and a new species of bivalve (Mollusca: Bivalvia) from Miocene hydrocarbon seep deposits, North Island, New Zealand - Saether, Kristian P.; Jingeng, Sha; Little, Crispin T. S.; Campbell, Kathleen A. (Zootaxa, 2016)
Fourteen bivalve taxa belonging to 11 families are present in at least 13 early to middle Miocene hydrocarbon seep deposits in the East Coast Basin, North Island, New Zealand. Among these are at least three new species, one of which, Semeloidea (s. l.) bexhavenensis sp. nov. (Lasaeidae), is described here. New distribution data are recorded for bivalve species in the families Limidae, Propeamussiidae, Malleidae and Solemyidae. Additional morphological details of Gigantidas coseli (Mytilidae) and Pratulum quinarium (Cardiidae) are provided based upon previously unrecorded internal shell features. Palaeoecological analysis indicates that bivalves utilized a broad range of modes of life and niches within the New Zealand Miocene seep environment, and no more than ca. 30% of these bivalve species were likely to have been obligate to seeps.